2019
DOI: 10.1038/s41598-019-55539-3
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-induced anxiety-like behavior is associated with disruption of medial prefrontal cortex - amygdala circuit

Abstract: Anxiety is prevalent in asthma, and is associated with disease severity and poor quality of life. However, no study to date provides direct experimental evidence for the effect of allergic inflammation on the structure and function of medial prefrontal cortex (mPFC) and amygdala, which are essential regions for modulating anxiety and its behavioral expression. We assessed the impact of ovalbumin (OVA)-induced allergic inflammation on the appearance of anxiety-like behavior, mPFC and amygdala volumes using MRI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…LFPs were simultaneously obtained from OB, EC, and dHPC via a fixed miniature buffer head stage with high-input impedance (BIODAC-A, TRITA Health Technology Co., Tehran, Iran). The signals were amplified using 1000 amplification gain, low-pass filtered < 250 Hz, and digitized at 1 kHz through a recording system (BIODAC-ESR18622, TRITA Health Technology Co., Tehran, Iran) 78 , 79 . EEG lab toolbox was applied for pre-processing the signals, including noise rejection and baseline correction 80 .…”
Section: Methodsmentioning
confidence: 99%
“…LFPs were simultaneously obtained from OB, EC, and dHPC via a fixed miniature buffer head stage with high-input impedance (BIODAC-A, TRITA Health Technology Co., Tehran, Iran). The signals were amplified using 1000 amplification gain, low-pass filtered < 250 Hz, and digitized at 1 kHz through a recording system (BIODAC-ESR18622, TRITA Health Technology Co., Tehran, Iran) 78 , 79 . EEG lab toolbox was applied for pre-processing the signals, including noise rejection and baseline correction 80 .…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study demonstrated that LPS causes anxiety and depression-like behaviors accompanied by an enhanced activity of the dmPFC-BLA circuits [ 12 ]. In addition, allergic inflammation leads to enhanced functional connectivity within the mPFC-amygdala circuit, while disrupting the dynamic interactions of the mPFC-amygdala circuit may promote anxiety-related behaviors with asthma [ 151 ]. Furthermore, a recent study from the same lab showed that allergic inflammation induced an increase in neuronal activity, and functional connectivity of the ACC-BLA circuit was correlated with the level of anxiety [ 152 ].…”
Section: Amygdala Neuroinflammation and Psychiatric Disordersmentioning
confidence: 99%
“…MPFC is activated by strong emotions (71). In addition, Dehdar et al (72) found that the prefrontal lobe of patients with asthma is related to the regulation of anxiety. This suggests that there may be a relationship between the function of respiration and the functional changes of MPFC in different emotional states.…”
Section: Discussionmentioning
confidence: 99%